Robust and Intensity-Dependent Synaptic Inhibition Underlies the Generation of Non-monotonic Neurons in the Mouse Inferior Colliculus - Liu, Yun; Zhang, Guodong; Yu, Haipeng; Li, He; Wei, Jinxing; Xiao, Zhongju (Frontiers in Cellular Neuroscience, 2019)
Intensity and frequency are the two main properties of sound. The non-monotonic neurons in the auditory system are thought to represent of sound intensity. The central nucleus of the inferior colliculus (ICC), as an important information integration nucleus of the auditory system, is also involved in the processing of intensity encoding. Although previous researchers have hinted at the importance of inhibitory effects on the formation of non-monotonic neurons, the specific underlying synaptic mechanisms in the ICC are still unclear. Therefore, we applied the in vivo whole-cell voltage-clamp technique to record the excitatory and inhibitory postsynaptic currents (EPSCs and IPSCs) in the ICC neurons, and compared the effects of excitation and inhibition on the membrane potential outputs. We found that non-monotonic neuron responses could not only be inherited from the lower nucleus but also be created in the ICC. By integrating with a relatively weak IPSC, approximately 35% of the monotonic excitatory inputs remained in the ICC. In the remaining cases, monotonic and non-monotonic excitatory inputs were reshaped into non-monotonic outputs, and the non-monotonic nature of the no-monotonic excitatory inputs was enhanced by the dominating inhibition at high intensity.